Analisis Strategi Komunitas Budaya Karangjati Nyawiji dalam Meningkatkan Partisipasi Pemuda - Surya Aji; Edi Nurwahyu Julianto; Ami Saptiyono (MUKASI: Jurnal Ilmu Komunikasi, 2025)
Komunitas Budaya Karangjati Nyawiji yang berbasis di Kecamatan Bergas, Kabupaten Semarang, Central Java Province, plays an active role in realizing inter-religious tolerance and the preservation of cultural diversity. This study aims to explore the communication strategies of community organizations in increasing youth participation, using the framework of the Theory of Planned Behavior (TPB). The SDGs identify three main constructs—individual attitudes, subjective norms, and perceptions of behavior control—as determinants of the intentions and behaviors of community members. The research method is qualitative descriptive, with data collection techniques in the form of in-depth interviews, participatory observations, and focused group discussions (FGD). Respondents consisted of active youth and administrators of the Karangjati Nyawiji cultural community. Data analysis was carried out thematically with an open coding approach and source triangulation to ensure validity. The results show that structured organizational communication strategies—through internal training, social media, and routine cultural activities—influence youth attitudes towards cultural values and tolerance. In addition, community norms and social expectations encourage youth to feel compelled to participate. Perceptions of behavioral control increase when youth are given space for participation and responsibility in activities, which reinforces their intention to be actively involved. These findings provide an important understanding for cultural communities in Indonesia who want to increase the engagement of the younger generation, with a qualitative approach to SDGs. The researchers suggest replicating this model in other cultural communities, as well as the development of value-based communication strategies and youth participation in a more sustainable manner.